Maternal age and risk of low birth weight and premature birth in children conceived through medically assisted reproduction. Evidence from Finnish population registers. Issue 1 (22nd January 2020) - Barbuscia, Anna; Martikainen, Pekka; Myrskylä, Mikko; Remes, Hanna; Somigliana, Edgardo; Klemetti, Reija; Goisis, Alice
Abstract: STUDY QUESTION: Does the risk of low birth weight and premature birth increase with age among mothers who conceive through medically assisted reproduction (MAR)? SUMMARY ANSWER: Among MAR mothers, the risk of poorer birth outcomes does not increase with maternal age at birth except at very advanced maternal ages (40+). WHAT IS KNOWN ALREADY: The use of MAR treatments has been increasing over the last few decades and is especially diffused among women who conceive at older ages. Although advanced maternal age is a well-known risk factor for adverse birth outcomes in natural pregnancies, only a few studies have directly analysed the maternal age gradient in birth outcomes for MAR mothers. STUDY DESIGN, SIZE, DURATION: The base dataset was a 20% random sample of households with at least one child aged 0–14 at the end of 2000, drawn from the Finnish population register and other administrative registers. This study included children who were born in 1995–2000, because the information on whether a child was conceived through MAR or naturally was available only from 1995 onwards. PARTICIPANTS/MATERIALS, SETTING, METHODS: The outcome measures were whether the child had low birth weight (LBW, <2500 g at birth) and whether the child was delivered preterm (<37 weeks of gestation). Conceptions through MAR were identified by examining data on purchases of prescription medication from the National Prescription Register. Linear probability models were used to analyse and compare the maternal age gradients in birth outcomes of mothers who conceived through MAR or naturally before and after adjustment for maternal characteristics (i.e. whether the mother suffered from acute/chronic conditions before the pregnancy, household income and whether the mother smoked during pregnancy). MAIN RESULTS AND THE ROLE OF CHANCE: A total of 56 026 children, 2624 of whom were conceived through MAR treatments, were included in the study. Among the mothers who used MAR to conceive, maternal age was not associated with an increased risk of LBW (the overall prevalence was 12.6%) at ages 25–39. For example, compared to the risk of LBW at ages 30–34, the risk was 0.22 percentage points lower (95% CI: −3.2, 2.8) at ages 25–29 and was 1.34 percentage points lower (95% CI: −4.5, 1.0) at ages 35–39. The risk of LBW was increased only at maternal ages ≥40 (six percentage points, 95% CI: 0.2, 12). Adjustment for maternal characteristics only marginally attenuated these associations. In contrast, among the mothers who conceived naturally, the results showed a clear age gradient. For example, compared to the risk of LBW (the overall prevalence was 3.3%) at maternal ages 30–34, the risk was 1.1 percentage points higher (95% CI: 0.6, 1.6) at ages 35–39 and was 1.5 percentage points higher (95% CI: 0.5, 2.6) at ages ≥40. The results were similar for preterm births. LIMITATIONS, REASON FOR CAUTION: A limited number of confounders were included in the study because of the administrative nature of the data used. Our ability to reliably distinguish mothers based on MAR treatment type was also limited. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study to analyse the maternal age gradient in the risk of adverse birth outcomes among children conceived through MAR using data from a nationally representative sample and controlling for important maternal health and socio-economic characteristics. This topic is of considerable importance in light of the widespread and increasing use of MAR treatments. STUDY FUNDING/COMPETING INTEREST(S): Funding for this project was provided by the European Research Council (grant no. 803959 MARTE to Alice Goisis and grant no. 336475 COSTPOST to Mikko Myrskylä). E.S. reports personal fees from Theramex, personal fees from Merck Serono, personal fees from Health Reimbursement Arrangement, non-financial support from Merck Serono and grants from Ferring, grants from Theramex, outside the submitted work. The remaining authors have no competing interests. TRIAL REGISTRTION NUMBER: N/A